Occurrence and characterisation of Mycobacterium avium complex in chicken and captive birds in selected states in Peninsular Malaysia - Sattar, Abdul (2018)
Avian mycobacteriosis is a chronic gastrointestinal disease of the birds. It is caused mainly by Mycobacterium avium complex (MAC) and Mycobacterium genavense. Almost all species of the birds are susceptible to mycobacteriosis. Mycobacterium avium complex is a group of opportunistic pathogens, which are ubiquitous in the environment. It consists of two closely related species; M. avium and M. intracellulare. Mycobacterium avium complex has a high public health significance and its prevalence in human and animals has reportedly been increasing throughout the world. It causes disseminated diseases in immunocompromised population, pulmonary infection in elder people and facial lymphadenitis in the children. In the birds, economic losses due to mycobacteriosis include low meat and egg production, high treatment costs and loss of endangered species of birds. Infected birds excrete MAC through their feces, therefore they (chicken and captive birds) may pose a zoonotic threat to immunocompromised owners. Avian mycobacteriosis is worldwide in distribution and is frequently reported from the northern temperate zone and to a lesser extent from the tropical areas. This study was conducted due to lack of recognized research about the occurrence of mycobacteriosis in chicken and captive birds in Peninsular Malaysia. This cross sectional study detected MAC by Ziehl-Neelsen (Z-N) staining, culture and direct PCR using 300 fecal samples from village chickens (n = 100), layer chickens (n = 100) and captive birds (n = 100). Due to small quantity of feces, 4 samples were excluded from culture and 58 samples (20 due to small quantity and 30 samples due failure in yielding PCR quality DNA) were excluded from direct PCR. Total number of fecal samples were 296 and 242 for microbiology and direct PCR respectively. Successful isolation of MAC on culture media mainly depends on decontamination of the samples. Even though several decontamination procedures are available, there is no consensus on a single procedure. Therefore, this study also aimed to evaluate six decontamination procedures for effective isolation of M. avium from spiked culture negative controls (village chickens n = 2) as well as fresh feces (chickens n = 35 captive birds n = 7). Decontamination procedures included (1) 4% NaOH, (2) 12% H2SO4 (3) 1% cetylperidinium chloride (CPC) (4) 4% NaOH-VNA, (5) 12% H2SO4 (6) CPC-VNA, (VNA referred to mixture of antibiotics containing vancomycin 100 μg/ml, nalidixic acid 100 μg/ml and amphotericin B 50 μg/ml). This study evaluated Löwenstein Jensen and calorimetric Middlebrook 7H9 culture media for rapid isolation of M. avium from spiked culture negative controls (layer chicken n = 4) and fresh feces (captive birds n = 45). Results of the evaluation of decontamination procedures revealed that CPC-VNA was the most favorable decontamination procedure for isolation of M. avium and other mycobacteria spp from feces. This method isolated mycobacteria from 2.4% fresh feces (chicken) and recovered 66.7% M. avium from spiked feces with 19% and 5.5% contamination of fresh fecal and spiked cultures respectively. This study also showed that CPC-VNA and L-J combination is the most favorable culture combination to isolate more mycobacteria with low contamination rate. This combination is cost effective, simple, reduces the workload on the bench and increases the recovery of M. avium from avian fecal samples. Results of the cross sectional study showed that all samples (296) were Z-N negative. Proportion of positive samples (by culture and PCR) was 4.0% (12/300). Proportion of Z-N positive cultures was 2.02% (6/296) and proportion of PCR positive samples was 2.5% (6/242). A total of 4% (4/100) village chickens and 2.08% (2/96) captive birds were found to be culture positive. Furthermore, PCR detected DNA of M. avium subspecies avium in 1.7% (1/58) feces from village chickens and 5.9% (5/84) feces from captive birds. No mycobacteria were isolated and detected in layer chickens. Sequence analysis confirmed three isolates (one IS901 and two 16S rRNA) as M. avium subspecies avium, M. terrae and M. engbaekii. Mycobacterium avium subspecies avium was isolated from a White Pelican (Pelecanus onocrotalus). Mycobacterium terrae and M. engbaekii were isolated from village chickens (Gallus domesticus). Direct PCR (IS901) detected DNA of M. avium subspecies avium in 2.5% (6/242) feces (chicken n = 1 and captive birds n = 5) and PCR results were further verified by sequencing. Mycobacterium avium subspecies avium DNA was detected in the feces of macaw parrot (n = 2) namely, Green Winged macaw (Ara chloropterus) and Blue and gold macaw (Ara ararauna), Cockatoo parrot (n = 2) namely, Umbrella cockatoo (Cacatus alba) and Galah cockatoo (Eolophus resicapilla), Black Hornbill Anthracoceros malayanus (n = 1) and village chicken Gallus domesticus (n = 1). Phylogenetic analysis of DNA sequences of M. avium subspecies avium obtained during this study revealed close relatedness to themselves and to M. avium strain RCAD0278. In conclusion, this study reports the occurrence of MAC in the chickens and captive birds in Peninsular Malaysia. Furthermore, this study also revealed that culture using CPC-VNA decontamination and direct PCR can be used as referential methods for detection of MAC and other members of genus Mycobacterium.